Microbiome of Pinus pinaster - Lopes, Helena de Fátima Silva (2018)
Pinus pinaster has a great environmental, historical and economical importance to Portugal. It represents the third place in occupation in forestry area. However, it has been losing area due to the modifications on land use, fires and diseases such as the pine wilt disease (PWD). Native from the North America the PWD has been spreading worldwide, it has spread through Asia and more recently was identified in Europe being detected in Portugal in 1999, representing a major threat to forests. Recently, the importance of the bacteria community to the PWD has been accessed and few studies address the microbiome of P. pinaster. Most of the existing studies uses culture-dependent techniques. This work aimed to reveal the bacterial community of healthy P. pinaster trees using culture-independent techniques. To observe the bacterial communities of healthy P. pinaster, stem samples from trees aged between 20 and 30 years were collected from 4 Portuguese locations: Comporta, Góis, Madeira Island and Vouzela. The trunks were cut into disks and the sawdust of the center of these disks were used to extract DNA. Samples were tested for the presence of the PWD nematode and all were negative. DGGE analysis was performed to compare the bacterial community of different samples and pyrosequencing was used to identify the community. After analyzing the DGGE profiles, a sample was cloned and sequenced, and the results showed that the most common and intense bands belonged to chloroplast genetic material. Pyrosequencing results had a great amount of reads belonging to chloroplast and they were eliminated from the study. With the pyrosequencing, six plyla were detected: Proteobacteria, Acidobacteria, Firmicutes, Bacteriodetes, Armatimonadetes and Actinobacteria. Proteobacteria was the most common, and from this plylum, Gammaproteobacteria was the most abundant class. Samples grouped by location and the location community differ significantly, only two OTUs were shared by all locations. Despite the low read number the bacterial community was characterized, and this information can be used for future studies.